Estimation Of The Carbon Value Of The Savana Ecosystem Of Wangi-Wangi Island Wakatobi Regency - Umar Ode Hasani; Sitti Marwah; Abdul Manan; La Baco; Dewi Fitriani (Jurnal Celebica : Jurnal Kehutanan Indonesia, 2024)
The purpose of this study was to determine the amount of carbon availability in the savanna ecosystem on Wangi-Wangi Island, Wakatobi Regency. This research was carried out in December 2023-January 2024, sampling in this research was carried out in the Wangi-Wangi Island Savana Ecosystem with an area of 2005.38 ha. Sampling used 15 plots. Determining the number of plots was based on the observation area which consisted of 5 separate locations, each location consisting of 3 plots so that 15 plots were obtained. Each location is given the symbol Location 1 (Komala Village), Location 2 (Matahora Village), Location 3 (Matahoran Village and Pookambua Village), Location 4 (Waetuno Village and Waelumu Village) and Location 5 (Liya Togo Village). The research results show that the availability of biomass in the Savana Ecosystem on Wangi-Wangi Island is 362,572.704 tons and the total carbon availability is 166,767.400 tons.